IN VITRO ANTIMALARIAL ACTIVITY AND TOXICITY STUDIES OF JOHAR (CASSIA SIAMEA) LEAVES FROM THREE DIFFERENT LOCATIONS - Tasiam, Ezrani; Primaharinastiti, Riesta; Ekasari, Wiwied (African Journal of Infectious Diseases (AJID), 2020)
Background: Antimalarial activity of Cassia siamea leaves has been proven by the active compound that has been found, i.e. Cassiarin A. It is known that the quantity of the content of a compound that has the potential as a raw material for medicine can be influenced by various factors including differences in plant origin. This study aims at comparing the antimalarial activity and toxicity of C.siamea leaves from three regions with different meters location values above sea level (asl), i.e Pariaman (1,000 m asl), Palu (60 m asl), and Surabaya (2 m asl). Materials and Methods: The materials used in this study were Johar leaves from Pariaman, Surabaya, and Palu extracted with n-hexane, and 90% ethanol containing 1% tartaric acid. The antimalarial activity test was done with Plasmodium falciparum 3D7. The toxicity test applied MTT ELISA method. Results: C.siamea leaf that had highest antimalarial activity came from Pariaman with IC50 value of 0.006μg/ml, then from Palu was 0.037μg/ml, and the lowest antimalarial activity was from Surabaya that was 0.09μg/ml . In testing the toxicity to get CC50, the highest toxicity came from Surabaya with CC50 value of 135.81μg/ml, Pariaman with CC50 value of 220.82 μg/ml, and the least toxic came from Palu with CC50 value of 235.52μg/ml . Conclusion: C.siamea leaf obtained from Pariaman had a selectivity index value that satisfies the requirements of a promising antimalarial effect.